Analysis of Volumetric Characteristics of Cold Emulsion Asphalt Mixtures on Closed and Open Gradation with Cement and Lime Filler Variations - I Dewa Made Alit Karyawan; Ratna Yuniarti; Desi Widianty; Fera Fitri Salsabila; Baiq Sulistia Furwati; Baiq Anggun Lola Santi (Postgraduate, University of Mataram, 2024)
Cold Emulsion Asphalt Mixture (CAED) uses unheated emulsified asphalt, thus reducing gas emissions and health risks for workers. Volumetric characteristics and aggregate gradation are very important to assess the quality of CAED. Therefore, the purpose of this study is to examine the volumetric characteristics of CAED, namely Void in Mix (VIM), Void in Mineral Aggregate (VMA), and Void Filled with Bitumen (VFB), with variations in filler (cement, lime) and aggregate gradation (dense, open). The study used a laboratory experimental method, including material preparation, sample preparation with five variations of filler, testing VIM, VMA, and VFB values, and data analysis. This study shows that the volumetric characteristics of CAED with closed and open gradations meet the VMA and VFB specifications, but the VIM value is only met in the closed gradation of CAED with a variation of 50% cement:50%. Better aggregate interlocking in closed gradations results in smaller air voids. Closed gradations are recommended for heavy traffic, while open gradations are suitable for well-drained roads and light traffic